Changes in the taxation of personal and corporate income in developed countries - Leoš Vítek (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2012)
Over the past ten years, the tax policies have responded in two stages: for the period of a swift economic growth by 2008, and during the rapid economic recession over the period of 2009–2010. In the first part of the paper, we summarise changes in the businesses environment in developed countries. In its second part, the paper discuses changes of the personal and corporate taxation in developed countries, their structure and impacts of the economic crisis on the tax revenues and tax structures. The last part analyses and discusses changes in the tax policy in the field of business and labour taxation. Our results show that the business taxation, compared to the personal taxation, depends stronger on the economic cycle. Although the structure of tax revenues in the developed countries has not changed significantly over the past ten years, decreasing of the personal and corporate tax rates has stopped.